Is Previous Upper Abdominal Surgery a Contraindication for Laparoscopic Cholecystectomy? - Katar, Mehmet Kağan (Cureus, 2021)
Background and objective In this era of minimally invasive surgery and enhanced recovery procedures, laparoscopic cholecystectomy (LC) is the prevailing treatment method for symptomatic cholelithiasis. However, there are some contraindications for this operation, such as a previous upper abdominal surgery. Additionally, the median conversion rate of LC is 5%. In this study, we aimed to investigate the effect of previous upper abdominal surgery on LC. Methods The study was designed as a single-center, retrospective, and observational analysis. A total of 277 LC patients were evaluated by classifying them into two groups - group A: those without previous upper abdominal surgery; group B: those with a history of previous upper abdominal surgery. Results Not surprisingly, the operation time and the degree of adhesions in group B were significantly higher compared to group A (p<0.001). On the other hand, there were no significant differences between the two groups in terms of complication rates, conversion rates, and the length of hospital stay (p=0.118, p=0.761, p=0.083, respectively). Conclusion LC is a safe method for cholelithiasis even in patients with a history of upper abdominal surgery. Previous upper abdominal surgery does not affect the conversion rates and length of hospital stay. Hence, previous upper abdominal surgery should not be accepted as a contraindication for LC.